2010
DOI: 10.1111/j.1432-2277.2010.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic influence of immunosuppressive drugs on small and large bowel transport and barrier function

Abstract: Summary Immunosuppressive drug (ISD)‐associated gastrointestinal disorders are a relevant risk factor for graft loss or patient death. The pathomechanisms and the incidence of post‐transplantation diarrhea remain to be fully understood. The aim of this study was to characterize the impact of cyclosporine A, tacrolimus (TAC), mycophenolate mofetil (MMF), enteric coated mycophenolic acid (EC‐MPA), sirolimus, everolimus (EVE) and fingolimod (FTY 720) on small and large bowel transport and barrier function. Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Clinical data show the occurrence of a significant number of drug-induced diarrhea incidences in liver and kidney organ transplanted patients receiving MPA therapy (Helderman and Goral, 2002; Malinowski et al, 2011; Krones and Hogenauer, 2012). Diarrhea can result in dehydration and discomfort in transplanted patients.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data show the occurrence of a significant number of drug-induced diarrhea incidences in liver and kidney organ transplanted patients receiving MPA therapy (Helderman and Goral, 2002; Malinowski et al, 2011; Krones and Hogenauer, 2012). Diarrhea can result in dehydration and discomfort in transplanted patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although glucose absorption in the intestines plays a crucial role in glucose homeostasis [ 13 ], it is unknown if intestinal glucose absorption is involved in the diabetogenic effect of TAC. According to a previous study, glucose malabsorption in the jejunum after TAC treatment was observed and the effect was dose-dependent [ 14 ]. Therefore, it is reasonable to hypothesize that intestinal glucose absorption participates in the diabetogenic TAC process.…”
Section: Introductionmentioning
confidence: 99%
“…The dosages used in rats are higher than those administered in humans because of the different body area‐to‐volume ratio and faster hepatic metabolism (Malinowski et al . ). Therefore, clinically relevant doses of immunosuppressants were selected in our study based on previous data and metabolic differences between rodents and humans (Malinowski et al .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, clinically relevant doses of immunosuppressants were selected in our study based on previous data and metabolic differences between rodents and humans (Malinowski et al . ). In addition, the solubility of ionizable drugs or pH‐responsive formulations is significantly influenced by the differences in pH along the GI tract and interspecies differences (Merchant et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation